142k views
15 votes
Inverse laplace of L^-1 {5s/s^2 + 3s - 4}​

User Johansson
by
6.3k points

1 Answer

11 votes

Answer:


L^(-1) ((5s)/(s^(2)+ 3 s -4 ) ) =
4e^(-4t) + e^(t)

Explanation:

Step(i):-

Given


L^(-1) ((5s)/(s^(2)+ 3 s -4 ) )

Factors of s² + 3s - 4

= s² + 4s - s -4

= s( s +4 ) -1 (s +4)

= (s-1)(s+4)


L^(-1) ((5s)/(s^(2)+ 3 s -4 ) )

=
L^(-1) ((5s)/(s+4)(s-1) ) )

By using partial fractions


((s)/(s+4)(s-1) ) ) = (A)/(s+4) + (B)/(s-1) ..(i)

s = A ( s-1) + B( s+4) ....(ii)

Put s= 1 in equation (ii) , we get

1 = B(5)


B = (1)/(5)

s = -4 in equation (ii) , we get

-4 = -5A


A =(4)/(5)

Step(ii):-

now the equation (i) , we get


((s)/(s+4)(s-1) ) ) = (4)/(5(s+4)) + (1)/(5(s-1))


L^(-1) ((s)/(s+4)(s-1) ) ) = 5( L^(-1) (4)/(5(s+4)) + 5L^(-1) (1)/(5(s-1))

By using inverse Laplace transform formula


L^(-1) ((1)/(s-a) ) = e^(at)


L^(-1) ((1)/(s-1) ) = e^(t)


L^(-1) ((1)/(s+4) ) = e^(-4t)


L^(-1) ((s)/(s+4)(s-1) ) ) = 5( L^(-1) (4)/(5(s+4)) + 5L^(-1) (1)/(5(s-1))

=
4e^(-4t) + e^(t)

User SGD
by
6.7k points